Bacterial composition of a competitive exclusion product and its correlation with product efficacy at reducing Salmonella in poultry - Lee, Margie D.; Pedroso, Adriana A.; Maurer, John J. (Frontiers in Physiology, 2023)
The mature intestinal microbiome is a formidable barrier to pathogen colonization. Day-old chicks seeded with cecal contents of adult hens are resistant to colonization with Salmonella, the basis of competitive exclusion. Competitive exclusion products can include individual microbes but are commonly undefined intestinal communities taken from adult animals and in commercial production is amplified in fermentator and sold commercially in freeze dried lots. While superior to single and multiple species probiotics, reducing Salmonella colonization by multiple logs, undefined products have limited acceptance because of their uncharacterized status. In this study, the bacterial composition of the master stock, preproduction seed stocks and commercial lots of a poultry competitive exclusion product, was defined by 16S rRNA sequence analysis, targeting the 16S rRNA variable region (V1-V3). The samples contained a diversity of genera (22-52 distinct genera) however, the commercial lots displayed less diversity compared to the seeds and the master stock. Community composition varied between seeds and the master stock and was not a good predictor of potency, in terms of log10 reduction in Salmonella abundance. While there was significant correlation in composition between seeds and their commercial lots, this too was a not a good predictor of potency. There was linear correlation between unclassified Actinobacteria, Peptococcus, and unclassified Erysipelotrichaceae and Salmonella abundance (r2 > 0.75) for commercial seeds. However, upon review of the literature, these three genera were not consistently observed across studies or between trials that examined the correlation between intestinal community composition and Salmonella prevalence or abundance.